2003
DOI: 10.17660/actahortic.2003.599.76
|View full text |Cite
|
Sign up to set email alerts
|

Application of Edible Coatings to Improve Shelf-Life of Mexican Guava

Abstract: One method of extending postharvest shelf-life is the use of edible coatings. Such coatings are made of edible materials that are used to enrobe fresh produce, providing a semipermeable barrier to gases and water vapour. Guavas cultivated at Aguascalientes, Mexico were coated with a solution of one of the following polymers: Potato starch, sodium alginate, carragenan, and pectin. The fruit was covered by immersion in the solution at 50°C, then dried at 50°C during 30 minutes. After coating, the maturation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…According to Rekha et al [6] 30-40% of initial ascorbic acid in some fruits can be lost on dehydration. To preserve the functional components and improve the product quality of foods, some pretreatment could be applied prior to drying [7]. Among various pretreatment methods, osmotic dehydration (OD) is traditionally applied to food dewatering which leads to attractive products.…”
Section: Introductionmentioning
confidence: 99%
“…According to Rekha et al [6] 30-40% of initial ascorbic acid in some fruits can be lost on dehydration. To preserve the functional components and improve the product quality of foods, some pretreatment could be applied prior to drying [7]. Among various pretreatment methods, osmotic dehydration (OD) is traditionally applied to food dewatering which leads to attractive products.…”
Section: Introductionmentioning
confidence: 99%
“…Application of various types of biopolymers as edible coatings on guava and apricot fruits showed that dextran and carboxymethylcellulose were more effective than polyethylene in retaining water and aroma compound (2-pentanone) of the fruit (17). Similarly, starch-and pectin-based coatings were also reported to improve the shelf life and aroma of Mexican guava (18). 'Valencia' oranges coated with commercial polysaccharidebased or shellac-based coatings exhibited higher concentrations of several aroma volatiles such as ethanol, ethyl butanoate, ethyl acetate, and R-pinene as compared to the untreated fruit (19).…”
Section: Introductionmentioning
confidence: 99%
“…At 25°C and between 50 and 70 percent of R.H., the coated fruit had a shelf life of at least three days longer than the untreated fruit. Potato starch and pectinbased coatings were shown to be the most effective in preserving the fruit's sensory features (size, yellow colour, and scent) for 15 days [51].…”
Section: Shelf-life Enhancement Of Guava (Psidium Guajava L) Fruit Us...mentioning
confidence: 99%